From Crisis to Resilience: How Female Adolescents Cope with Early Marriage Resulting from Unplanned Pregnancy - Eli Nuzul Wahyuni; Abdul Haris Fitri Anto; Nova Lusiana (International Conference on Sustainable Health Promotion, 2025)
Early marriage due to “Married by Accident” is a phenomenon that creates various emotional, social, and financial challenges for adolescents, which may affect their psychological well-being and prospects. This study aims to explore the experiences and coping strategies employed by young women who entered early marriage as a result of unplanned pregnancy. A qualitative method with a case study approach was applied, involving three participants who met the inclusion criteria. Data were collected through semi-structured interviews and analysed using thematic analysis. The findings indicate that all three participants adopted two forms of coping strategies: problem-focused coping and emotion-focused coping. Problem-focused coping was reflected in efforts to seek medical information, prioritise plans for continuing education, and take practical steps to meet family needs. Meanwhile, emotion-focused coping appeared in their ability to accept circumstances, find positive meaning in the experience, and obtain emotional support from family and spouses. These results highlight that the combination of effective coping strategies and social support plays an essential role in helping adolescents deal with psychosocial pressures arising from early marriage due to unplanned pregnancy.